PENGARUH DIFERENSIASI PRODUK DAN HARGA PONSELGSM TERHADAP KEPUTUSAN PEMBELIAN: Survei Terhadap Pengguna Ponsel GSM di Bandung Electronic Centre - Cecep Andritela Firdaus, - (2007)
Cecep Andritela Firdaus, S.Si. (054243). The Influence of Product Differentiation and Price of GSM Cellular Phone Toward Buying Decision. Under the guidance of Dr. Agus Rahayu, M.Si. and Dr. Vanessa Gaffar, SE.Akt., MBA. The declining growth of GSM cellular phone user indicates that there has been a decline in the buying decision. It is assumed that product differentiation and price of GSM cellular phone are not working properly. The objective of the research is to know the influence of product differentiation and price of GSM cellular phone toward buying decision. This is a descriptive and a verificative research. Therefore using explanatory survey. The sample of this research is 100, using systematic sampling technique taken from the population which is 96.000 those who bought GSM cellular phone in new condition. Data analysis technique used is path analysis with AMOS 5.0. The research shows that coefficient path between product differentiation toward GSM cellular phone buying decision is 30,4% indicates the the influence is low It shows that the advantage of product differentiation of GSM cellular phone is still low Meanwile, GSM cellular phone price estimated 8,18% in influencing GSM cellular phone buying decision. This indicates that GSM cellular phone price has a very low influence to consumer buying decision. It shows that GSM cellular phone price is not a decisive factor to GSM cellular phone buying decision. Overall, 49,7% GSM cellular phone buying decision is influenced by product differentiation and GSM cellular phone price of GSM cellular phone. In this case, the influence of product differentiation and price of GSM cellular phone toward buying decision is on the average level which is about 50,3% is influenced by another variables which cannot be explained on this research. From the effectivity of the model, this model is more compatible to male group sample who have salary more than Rp. 1.000.000,01 per month. Thus, the producent of GSM cellular mobile phone should be more focus to this segment.